2019
DOI: 10.1038/s41598-019-44302-3
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dependent effects of chronic alcohol drinking on peripheral immune responses

Abstract: It is well established that chronic heavy alcohol drinking (CHD) results in significant organ damage, increased susceptibility to infections, and poor outcomes following injury. In contrast, chronic moderate drinking (CMD) has been associated with improved cardiovascular health and immunity. These differential outcomes have been linked to alterations in both innate and adaptive branches of the immune system; however, the mechanisms remain poorly understood. To address this question, we determined the impact of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
84
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(91 citation statements)
references
References 72 publications
7
84
0
Order By: Relevance
“…Chronic ethanol abuse almost doubles the risk of developing acute respiratory distress syndrome [ 59 ]. The association between bacterial and viral lung infections and ethanol dependence is supported by multiple pathophysiological mechanisms [ 60 , 59 , 61 ]:…”
Section: Alcohol Consumption Immune System and Covid-19mentioning
confidence: 99%
“…Chronic ethanol abuse almost doubles the risk of developing acute respiratory distress syndrome [ 59 ]. The association between bacterial and viral lung infections and ethanol dependence is supported by multiple pathophysiological mechanisms [ 60 , 59 , 61 ]:…”
Section: Alcohol Consumption Immune System and Covid-19mentioning
confidence: 99%
“…Moreover, our DEG analysis, suggested two genes, Elovl6 and Sult2a3, changed by exposure of alcohol in both diets (diet-independent) that can potentially be used to design alcohol specific, diet independent, drug targeting but also potential diet independent biomarkers of alcohol toxicity. www.nature.com/scientificreports www.nature.com/scientificreports/ Previous published work showed that alcohol effects on immune system are dependent of the duration and dose of alcohol exposure as well as gender and age of mice, so our present comparative work between these two most common murine chronic models used to study the effect of alcohol has some limitations 19,54,55 .…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, chronic alcohol drinking increases inflammatory transcriptomic profile following LPS stimulation in peripheral blood mononuclear cells in dose dependent manner 54 . A confounding factor in our study is that the amount of alcohol per day consumed in LD model was higher compared with MC model in spite of more extended time of alcohol exposure in MC mice.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the pro-inflammatory impact of drinking was significant only with chronic heavy alcohol drinking. These transcriptional changes are being claimed to be partially explained by alterations in microRNA profiles (Sureshchandra et al 2019a).…”
Section: Cancermentioning
confidence: 99%